2020
DOI: 10.3389/fmicb.2020.00229
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Oxidation State in Microbial Polar Lipids Suggests Adaptation to Hot Spring Temperature and Redox Gradients

Abstract: The influence of oxidation-reduction (redox) potential on the expression of biomolecules is a topic of ongoing exploration in geobiology. In this study, we investigate the novel possibility that structures and compositions of lipids produced by microbial communities are sensitive to environmental redox conditions. We extracted lipids from microbial biomass collected along the thermal and redox gradients of four alkaline hot springs in Yellowstone National Park (YNP) and investigated patterns in the average oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 103 publications
1
27
0
Order By: Relevance
“…We further examine, for the first time, the impact of agitation on GDGT cyclization. Higher temperatures yielded higher average cyclization, which is consistent with most experimental studies of both Thaum- and Crenarchaeota (912, 24, 25), yet opposes recent environmental findings in alkaline hotsprings (26). When pH deviated from the optimum pH of ∼3 for DSM639, cyclization decreased.…”
Section: Discussionsupporting
confidence: 88%
“…We further examine, for the first time, the impact of agitation on GDGT cyclization. Higher temperatures yielded higher average cyclization, which is consistent with most experimental studies of both Thaum- and Crenarchaeota (912, 24, 25), yet opposes recent environmental findings in alkaline hotsprings (26). When pH deviated from the optimum pH of ∼3 for DSM639, cyclization decreased.…”
Section: Discussionsupporting
confidence: 88%
“…1 m deep hypersaline, oxygenated water (approximately 200 mM O 2 ), but in the mat, oxygen rises during the daytime and is depleted within a few millimeters, giving way to anoxic, then sulfidic conditions (Ley et al, 2006 Using metagenomic data for these redox gradients (Kunin et al, 2008;Havig et al, 2011;Swingley et al, 2012;Reveillaud et al, 2016;Fortunato et al, 2018), Dick et al (2019) showed that the carbon oxidation states of DNA, messenger RNA, and proteins increase down the outflow channel of Bison Pool and between fluids from diffuse hydrothermal vents and relatively oxidizing seawater. Notably, intact polar lipids extracted from the microbial communities of Bison Pool and other alkaline hot springs also exhibit downstream increases in carbon oxidation state (Boyer et al, 2020), confirming that similar trends characterize multiple classes of biomolecules. The Z C of proteins increases more subtly toward the surface in the upper few millimeters of the Guerrero Negro microbial mat; it also increases at greater depths, perhaps due to heterotrophic degradation and/or horizontal gene transfer (Dick et al, 2019).…”
Section: Comparison Of Redox and Salinity Gradientsmentioning
confidence: 60%
“…The high abundance of SRB at the end of the slurry incubations and the positive correlation between PE IPLs and high-sulfate condition ( Figure S8) might indicate that the occurrence of PE can be linked to the presence of SRB in enrichment slurries. The presence of trimethylornithine (TMO) IPLs in three butyrate-amended slurries from the methane zone ( Figure S7, Table S4) was surprising since these lipids were originally identified in planctomycete isolates from ombrotrophic northern wetlands [49], and later observed in northern wetland peat [50], meso-oligotrophic lakes of Minnesota and Iowa [51], and Yellow Stone National Park hot spring microbial communities [52]. No planctomycete phylotypes were detected in any of the butyrate-amended methane zone-derived slurries, indicating that the observed TMOs were produced by other microbial groups or the relative abundance of planctomycete phylotypes was very low.…”
Section: Bacterial and Archaeal Community Structure In The Enrichmentmentioning
confidence: 99%